The responses of Some Morphological and Physiological characters in one Canola (Brassica napus L.) Cultivars to Soil Water Stress - H Noorani azad,; M.R Hajibagheri, (فیزیولوژی محیطی گیاهی, 2009)
In order to study the morphologic and physiologic responses of one Canola cultivar (Talayie) to moisture Stress, a 4- replicate CRD greenhouse experiment was conducted during at the Islamic Azad University of Jahrom. The treatments consisted of five moisture levels with intervals 7(control),14,21,28 and 35 days of irrigation .Total dry weight, stem length and root, total leaf chlorophyll, total soluble sugars and proline, Na+, K+ in leaves were measured at the final leaf growth stage. Results showed that total leaf chlorophyll and K+ significantly decreased in comparison to control. Dry weight decreased with increasing drought stress and significantly decreased in treatments of 28 and 35 day of irrigation in comparison to control. Decrease of stem length, except in treatment of 14 day of irrigation has significant in comparison to control. Na+ in leaves significantly increased with increasing of drought stress. The differences of root length between different treatments were not significant. The total soluble sugars and proline contents increased with increasing of drought stress. The sugars and proline accumulation probably play an important role in the osmoregulation and induction of drought tolerance. Decrease of k+may be lead to stomatal resistance and decreasing of photosynthesis and growth.